The Effect of Current Ratio, Total Asset Turnover and Return on Asset on Profit Growth in Manufacturing Companies Listed on the Indonesia Stock Exchange - Handayani, Ridho Noor; Lahaya, Ibnu Abni (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to determine the effect of Current Ratio (CR), Total Asset Turnover (TATO), and Return On Asset (ROA) on profit growth in manufacturing companies listed on the IDX. Prediction of profit growth is very important for investors in making investment decisions. The sample used in this study were 84 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period, in order to obtain 252 company data. The data analysis technique used multiple linear regression analysis. Data processing used the Statistical Package for Social Science version 23 (SPSS 23) program. The results of this study indicate that the variable Current Ratio (CR) has a negative and significant effect on the profit growth of manufacturing companies, Total Asset Turnover (TATO) and Return On Asset (ROA) have a negative and insignificant effect on the profit growth of manufacturing companies